Intellectual capital as a mediator between corporate governance and sustainability initiative: a conceptual review - Adedeji, Babatunji Samuel; Ong, Tze San; Rahman, Mohammad Mizanur (Inderscience, 2020)
This review has conceptualised the integration of corporate governance (CG) and intellectual capital (IC) as strategic tools for enhancing sustainability initiative (SI) locally and internationally by scholars and practitioners. Since, CG tools are institutional factors required to prolong the life span of corporate organisations, then IC can further play a boundless role in ensuring the resourceful and effective transformation of the firms at large. The resource-based view, institutional, agency and stakeholder theories or a mix of them can be adopted for empirical study purposes. This study opines that there might be a direct relationship between CG and SI and IC and SI on one hand, and the mediating role of IC in the relationship between CG and SI on the other hand to examine the indirect and total effects which are suggested be tested using the covariance based-structural equation modelling (CB-SEM) technique.